Cost-effectiveness analysis of adebrelimab combined with chemotherapy for extensive-stage small cell lung cancer - You, Maojin; Chen, Ruijia; Wu, Qingfeng; Zhu, Wei; He, Ying; Huang, Yufan (Frontiers in Pharmacology, 2022)
Background: The findings of the CAPSTONE-1 trial showed that adebrelimab in combination with chemotherapy (etoposide-carboplatin) (ADCHM) is clinically beneficial as a first-line treatment for patients with extensive-stage small cell lung cancer (ES-SCLC), compared with placebo plus chemotherapy (PLCHM, etoposide-carboplatin). However, owing to the higher cost of adebrelimab, it is unclear whether ADCHM is cost-effective compared with PLCHM. This study aimed to evaluate the cost-effectiveness of ADCHM as a first-line treatment for patients with ES-SCLC from the perspective of the Chinese healthcare system. Methods: A Markov model with three health states was developed to assess the cost-effectiveness of ADCHM as a first-line treatment option with ES-SCLC. Clinical data were obtained from the CAPSTONE-1 trial. Costs of the drug were calculated at national tender prices, and other costs and utility values were obtained from published literature. The outcomes included life years (LYs), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). One-way sensitivity analysis and probabilistic sensitivity analysis were used to validate the robustness of the model. Results: The ADCHM group achieved 1.21 QALYs (2.47 LYs) for 25,312, whereas the PLCHM group achieved 0.81 QALYs (1.59 LYs) for 14,846. The ICER for ADCHM versus PLCHM was 25914 per QALY gained. The variables with the greatest impact on the model results were the utility value of progressive disease, the utility value of progression-free survival, and the price of adebrelimab (100 mg). At a willingness-to-pay threshold of 37,653/QALY, ADCHM had an 89.1% probability of being cost-effective compared with PLCHM. Conclusions: ADCHM may be a cost-effective first-line treatment strategy for ES-SCLC from the perspective of the Chinese healthcare system.